Enucleated eyes after failed intra-arterial infusion of chemotherapy for unilateral retinoblastoma: histopathologic evaluation of vitreous seeding - Kim JW (Dove Medical Press, 2011)
Jonathan Kim1, Huy Do2, Peter Egbert11Department of Ophthalmology, Stanford Medical Center, Palo Alto, CA, USA; 2Department of Interventional Neuro-radiology, Stanford Medical Center, Stanford, CA, USAAbstract: Selective intra-arterial chemotherapy (IAC) has been adopted by many ocular oncology centers to treat advanced intraocular retinoblastoma. In this report, we describe two patients with unilateral intraocular retinoblastoma and persistent vitreous seeding, who were treated with IAC after failed systemic chemotherapy. Despite multiple sessions and increasing dosage of drug delivery, vitreous seeding in these cases failed to respond to IAC, and ultimately both eyes were enucleated for tumor control. Based on the histopathologic findings in these two cases, IAC appears to have limitations in treating persistent vitreous seeding in eyes which have failed systemic chemotherapy. Possible causes for failure of IAC to treat persistent vitreous seeding include poor vitreous penetration, inactive state of tumor seeds within the avascular vitreous cavity, and chemotherapeutic drug resistance.Keywords: chemotherapy, retinoblastoma, intra-arterial, failure, enucleation, eye